Density measurements with computed tomography in patients with extra-axial hematoma can quantitatively estimate a degree of brain compression. Issue 5 (October 2016) - Nguyen, Ha Son; Li, Luyuan; Patel, Mohit; Mueller, Wade
Background: Extra-axial hematoma can cause significant brain compression. Guidelines for surgical evacuation include imaging findings (midline shift and hematoma thickness/volume) in conjunction with Glasgow Coma Scale (GCS) scores and/or intracranial pressure (ICP) monitoring. Physiologically, overall brain density should also change with compression. In our observational study, we explored whether overall brain density, defined using computed tomography Hounsfield Units (CT HU), changes after surgical evacuation of extra-axial hematoma. Methods and materials: Only patients with a surgical acute epidural hematoma or subacute/chronic subdural hematoma were considered. Other exclusion criteria were concurrent intraparenchymal pathology, bilateral pathology, or incomplete follow-up imaging. Between fall 2012 and spring 2015, 22 patients were included in the study. CT head imaging (preoperative, postoperative, and at ∼1- to 2-month clinic visit) were loaded into OsiriX (Pixmeo, Switzerland). All the intracranial regions were selected and all extra-axial features were removed; subsequently, software was used to calculate a global CT HU value. Results: A repeated-measures ANOVA found significant time effect, p  < 0.01, with significance between preoperative versus postoperative CT ( p  = 0.03) and preoperative versus clinic visit CT ( p  < 0.01). Conclusion: The results from this study suggest that extra-axial hematomas, which deform the brain, can cause an elevation in global CT HU value; moreover, surgical decompression is associated with lower global CT HU values. The use of global CT HU values in selected populations may serve as an adjunct for the evaluation of surgical lesions.